Application Of The Internet Of Things (IoT) In Production Management To Increase Production Efficiency In The Digital Era - Suwanda, Suwanda (Jurnal Ekonomi, 2024)
The digital era has brought significant changes to the production process, where the use of information technology and automation has become a key factor in increasing productivity and operational efficiency. This research aims to examine the application of the Internet of Things (IoT) in effective production management in increasing production efficiency in the digital era. This research uses a qualitative approach with descriptive methods. The research results show The use of the Internet of Things (IoT) in production management significantly increases efficiency by leveraging real-time monitoring, big data analysis, and connected system integration. IoT enables continuous monitoring of machine conditions through sensors, which helps detect problems early, perform predictive maintenance and optimize machine performance. Accurate and up-to-date data enables fast, data-driven decision making and rapid response to production disruptions. In addition, IoT makes it easier to document and analyze problems as well as systematic repairs, increasing maintenance effectiveness and production quality. However, IoT implementation also faces challenges such as data security, system integration, implementation costs, device interoperability, and dependency on network infrastructure. Managing these challenges well is important to harness the full benefits of IoT technology in improving production efficiency.